A randomized phase 2 trial of gemcitabine/cisplatin with or without cetuximab in patients with advanced urothelial carcinoma. Issue 17 (6th May 2014) - Hussain, Maha; Daignault, Stephanie; Agarwal, Neeraj; Grivas, Petros D.; Siefker‐Radtke, Arlene O.; Puzanov, Igor; MacVicar, Gary R.; Levine, Ellis Glenn; Srinivas, Sandy; Twardowski, Przemyslaw; Eisenberger, Mario A.; Quinn, David I.; et al.
Abstract : BACKGROUND: Epidermal growth factor receptor overexpression is associated with poor outcomes in urothelial carcinoma (UC). Cetuximab (CTX) exhibited an antitumor effect in in vivo UC models. The efficacy of gemcitabine/cisplatin (GC) with or without CTX in patients with advanced UC was evaluated. METHODS: Patients with advanced UC, measurable disease, and adequate organ function were randomized 1:2 to cisplatin (70 mg/m 2 ) on day 1 plus gemcitabine (1000 mg/m 2 ) on days 1, 8, and 15 (arm A) or GC plus CTX (500 mg/m 2 ) on days 1 and 15 (arm B). The primary endpoint was the overall response rate. The secondary endpoints were the response duration, safety, progression‐free survival, overall survival, determination of whether or not CTX sensitized nonresponders to GC, and exploratory biomarker analysis. The accrual targets were 27 and 54 patients for the 2 arms, respectively. The overall response rate was reported by arm with binomial confidence intervals (CIs). Kaplan‐Meier methods were used for time‐to‐event endpoints. RESULTS: Eighty‐eight eligible patients were randomized; 87 were toxicity‐evaluable, and 85 were response‐evaluable. The overall response rates were 57.1% for arm A (95% CI = 37%‐76%) and 61.4% for arm B (95% CI = 48%‐74%). The median progression‐free survival times were 8.5 months for arm A (95% CI = 5.7‐10.4 months) and 7.6 months for arm B (95% CI = 6.1‐8.7 months). The median overall survival times were 17.4 months for arm A (95% CI = 12.8 months to unreached) and 14.3 months for arm B (95% CI = 11.6‐22.2 months). The most common grade 3/grade 4 adverse events in both arms were myelosuppression and nausea. Thromboembolism, acneiform rash, fatigue, pain, hypersensitivity reactions, elevated transaminases, hyponatremia, and hypomagnesemia were more common in arm B; 3 grade 5 adverse events occurred in arm B. The presence of primary disease significantly correlated with thromboembolism. An increased soluble E‐cadherin level after cycle 2 correlated with a higher risk of death. CONCLUSIONS: GC plus CTX was feasible but was associated with more adverse events and no improvements in outcomes. Cancer 2014;120:2684–2693. © 2014 American Cancer Society . Abstract : The combination of cetuximab and gemcitabine/cisplatin is feasible. The combination does not appear to improve response rates in patients with advanced urothelial carcinoma.